2014
DOI: 10.1177/0003319714544947
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patients With Diabetes Having Normal Coronary Arteries

Abstract: We evaluated the association between risk variables in diabetic patients with normal and diseased coronary arteries in a retrospective cohort study conducted at Rashid Hospital, Dubai. A total of 4446 patients underwent coronary angiography due to various indications; 43% had type 2 diabetes mellitus (T2DM). Among the diabetic patients, 94% had diseased coronary arteries and the remaining 6% had absolutely normal arteries. The normal coronary group had significantly lower low-density lipoprotein cholesterol (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…In a study of 98 asymptomatic individuals with T2DM without known CAD, Rassi et al (23) found a significant number (44%) had CAD based upon CTA. In contrast, Binbrek et al (24) found that only 5.5% of 1902 patients with T2DM in Dubai had normal coronary arteries. In the latter study, the group with normal coronary arteries had significantly lower LDL-C and higher HDL-C levels compared to the diseased group.…”
Section: Comparison To Previous Studiesmentioning
confidence: 89%
“…In a study of 98 asymptomatic individuals with T2DM without known CAD, Rassi et al (23) found a significant number (44%) had CAD based upon CTA. In contrast, Binbrek et al (24) found that only 5.5% of 1902 patients with T2DM in Dubai had normal coronary arteries. In the latter study, the group with normal coronary arteries had significantly lower LDL-C and higher HDL-C levels compared to the diseased group.…”
Section: Comparison To Previous Studiesmentioning
confidence: 89%
“…1 This difference may be due to higher postprandial glucose levels raising the HbA 1c . Unfortunately, postprandial glucose levels in the Binbrek et al study were not specified.…”
mentioning
confidence: 99%
“…Unfortunately, postprandial glucose levels in the Binbrek et al study were not specified. 1 There is a study showing that the severity of coronary artery disease (CAD) is related to high postprandial glucose. 3 Several studies reported that postprandial glucose levels were more related to cardiovascular mortality than fasting plasma glucose.…”
mentioning
confidence: 99%
See 2 more Smart Citations